Colorimetric and Fluorescence Dual-Mode Biosensors Based on Peroxidase-Like Activity of the Co3O4 Nanosheets - Tan, Jingying; Geng, Weifu; Li, Junde; Wang, Zhen; Zhu, Shaohao; Wang, Xiuzhong (Frontiers in Chemistry, 2022)
The mimic enzyme has become a research hotspot in recent years because of its advantages of high stability, convenient preparation, and low price. In this article, Co3O4 nanosheets synthesized by a simple hydrothermal method possess the characteristics of a peroxidase-like activity. The results demonstrated that 3,3′,5,5′-Tetramethylbenzidine (TMB) could be oxidized by H2O2 to produce a typical blue product (oxTMB) which has a strong absorption at 650 nm wavelength with the help of the Co3O4 nanosheets. Thus, a simple and sensitive colorimetric detection method for H2O2 was established with a good linear relationship (2–200 μM) and a low limit of detection (0.4 μM). Meanwhile, the colorimetric product can effectively quench the fluorescence emitted by Ru(bpy)32+. Therefore, a colorimetric and fluorescence dual detection mode photochemical sensor for H2O2 detection is constructed based on the principle of the inner filter effect (IFE) between the colorimetric product (oxTMB) and Ru(bpy)32+. It can effectively avoid the false positive problem of a single detection mode. In the presence of glucose oxidase, glucose can be catalyzed to produce gluconic acid and H2O2; therefore, the sensor can also be used for the determination of glucose with a good linear relationship (0.02–2 μM) and a low limit of detection (5 nM). Experimental results showed that the sensor has a high sensitivity and strong anti-interference ability which can be used for the detection of actual samples.